Extracellular Biosynthesis of Silver Nanoparticles by Endophytic Fungus Aspergillus terreus and its Anti dermatophytic Activity - M Kalaiselvam, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Extracellular Biosynthesis of Silver Nanoparticles by Endophytic Fungus Aspergillus terreus and its Anti dermatophytic Activity